TRANING OF SENAM INDONESIA BERSATU TO IMPROVE THE PHYSICAL FITNESS FOR JUNIOR HIGH SCHOOL TEACHER IN ACEH TIMUR DURING THE PANDEMIC OF COVID 19 - Muhammad Arif Fadhilah; Yoki Afriandy Rangkuti; Rizkei Kurniawan (Global Science Society, 2022)
This service aims to provide assistance in the form of United Indonesia Gymnastics training. This is done as an effort to improve the fitness and body immunity of educators, education staff, and students in the school environment in East Aceh Regency. The main output designed is a service article related to the activities carried out. Furthermore, the product designed is the availability of video tutorials along with exercise instruction booklets.